The Successful Elements Implementing the eLearning using Cloud Services Data Centre at Private Institution of Higher Learning in Malaysia - Azlinda Abdul Aziz; Setyawan Widyarto; Salyani Osman; Suziyanti Marjudi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
There are a few network environment used for institutions of higher learning for eLearning application. The world financial crises cause institution of higher learning struggling to maintain and update the technologies and infrastructures and try to provide the sufficient budget allocation for the network infrastructure. Cloud Services Data Centre network environment is one of the solution where they does not used physical network technology and infrastructure and cost saving. The purpose of this paper is to identify the success factor elements in implementing the eLearning using Cloud Services Data Centre at Private Institution of Higher Learning in Malaysia. The literature was reviewed and base on the preliminary study a few elements was identified for the success factor elements. The elements are perception, business needs, strategy planning, cost saving, security and vendor capability. Base on the finding the propose framework and hypothesis was derived. To validate the success factor elements of Cloud Services Data Centre the pilot test was been done.